Pediatricians adherence to immunoprophylaxis of infectious diseases: current state of the problem - A.A. Garina; F.I. Petrovski; A.L. Zaplatnikov (LCC «Medicine-Inform», 2020)
A.A. Girina1, F.I. Petrovski1, A.L. Zaplatnikov2 1Khanty-Mansiysk State Medical Academy, Khanty-Mansiysk, Russian Federation 2Russian Medical Academy of Continuous Professional Education, Moscow,  Russian Federation In 2019, the World Health Organization (WHO) for the first time included refusal of vaccination in the list of ten global threats to humanity, since a decrease in vaccination coverage can trigger breakouts of many preventable infectious diseases. Aim: to clarify the causes for insufficient doctors' adherence to immunoprophylaxis of infectious diseases and to develop measures for eliminating these causes.  Patients and Methods: an open pilot online survey of 175 pediatricians working in medical institutions of the Khanty-Mansiysk Autonomous Okrug-Yugra (KMAO-Yugra) was conducted. The questionnaire contained 14 questions about the respondents' attitude to various aspects of vaccinal prevention, as well as the level of respondent training on this topic. At the same time, a point scale was used to evaluate the provisions offered to the respondent for analysis (the minimum score is 0 points, the maximum score is 5 points). Results: 71-76% of responde nts were convinced of the vaccination efficacy and safety. The main reasons for the lack of adherence to immunoprophylaxis of infectious diseases among the surveyed pediatricians were the insufficient level of knowledge due to the lack of continuous medical education on vaccinal prevention during the entire period of professional activity (25% of hospital-based physicians, 20% of doctors of educational institutions, 16% of health officials and 9% of general practitioners) and the use of information obtained from unofficial sources presented in the global Internet (25% of respondents). The study found that 13% of the physicians surveyed were not familiar with the recommendations for vaccination of pregnant women against influenza, and 24% were not informed about the possibilities, efficacy and safety of pregnant women vaccination against pertussis. Methods to increase the pediatricians' adherence level to vaccination are outlined, the key among which is mandatory periodic professional development in immunoprophylaxis of infectious diseases in the system of continuing professional education. Conclusion: almost every fifth pediatrician of the KMAO-Yugra surveyed has an insufficient adherence level to immunoprophylaxis of infectious diseases. The article outlines the methods to increase the pediatricians' adherence level to vaccination. Keywords: vaccination, pediatrician, immunoprophylaxis, continuing professional education, vaccination coverage, continuing education, adherence to vaccination. For citation: Girina A.A., Petrovski F.I., Zaplatnikov A.L. Pediatricians adherence to immunoprophylaxis of infectious diseases: current state of the problem. Russian Journal of Woman and Child Health. 2020;3(4):290-294. DOI: 10.32364/2618-8430-2020-3-4-290-294.